The Differences Between Atheists and Agnostics: A Comparison of Various Attitudes - Kenan Sevinç (Türkiye Din Eğitimi Araştırmaları Dergisi)
Many studies show that there are different types of nonbelief. Some of them define atheism and agnosticism as two different types of nonbelief, while others see agnosticism as a form of atheism. This paper deals with the differences in attitudes of atheists and agnostics on various issues. In order to detect this difference, the dataset of “International Social Survey Programme: Religion IV (ZA7570_v2.1.0)” on religion and values was used. The data were downloaded from gesis.org and analyzed. Survey data were collected by GESIS (n=46267) from 33 countries between 2017 and 2020. The number of atheists and agnostics is 11759 (58.4% atheist). The two groups were compared in terms of demographics, attitudes towards religion, sexual attitudes, political preference, trust in science, and happiness. The results of the analysis show that atheists and agnostics have different attitudes on many issues and that atheists are more true believers than agnostics.